Present Academic Status of the Department of Medicine in Different Medical Colleges of Bangladesh (Journal of Medicine, 2015)
Background: Medicine is said to be the father of Medical education. The clinical phase of education of a medical student should be done in an academically oriented hospital specially Medicine Department. Lack of adequate clinical exposure must leads to inadequate learning. Methods: A cross-sectional study was done to look into the present academic scenario of the department in different Medical Colleges of Bangladesh. Here the Medicine Department of all the Medical Colleges was included; of them 22 were government and 44 were private. The allied branches were excluded. The concerned department of all the Medical Colleges was offered a prestructured questionnaire. 27 of them replied; 13 were public & 14 were private. They were regarded as Code A & Code B respectively. Results: We found that the number of functioning unit is less than requirement in Code B(2.31). Though the student bed ratio is adequate; the number of midlevel teacher is much less in both the codes. Office secretary is lacking as well as the ward side minilab facility. Most of the conference rooms are shared. There is a great vacuum regarding the integrated teaching class. We also noted that the publication & presentation is much less in Code B. Conclusion: With the rapid growth of Medical education, the need for promoting ethical medical practice is mandatory. So the lacking of existing medical content should be fulfilled in an urgent manner.DOI: http://dx.doi.org/10.3329/jom.v16i1.22372 J MEDICINE 2015; 16 : 5-9